Identification and Source Apportionment of Air Particulates and Its Elemental Composition in Different Microenvironments of a Mega City: A Case Study of Lagos, Nigeria - J. M. Okuo; F. O. Oyibo; B. Anegbe; I. E. Chiedu; O. Adeniyi; W. Ojo (Newest Updates in Physical Science Research Vol. 1, 2021)
Lagos State, Nigeria, like most megacities globally, is faced with deteriorating air quality as a result of rapid industrialization, accelerated urbanization, economic development, unprecedented population growth, poor town planning and lax/non enforcement of laws governing air quality standards. This study aims at investigating Total Suspended Particulates (TSP), its elemental concentrations and source emission signatures in the indoor and outdoor microenvironments of a residential area in Lagos State. Samples were collected from July 2016 to April 2017 with the aid of a portable air sampler (Hi-Q CF – 901). Thereafter, the weight of the samples were determined by gravimetric method. The elemental content of the samples were then extracted by wet acid digestion method and quantified by Atomic Absorption Spectroscopic (AAS) method. In order to identify the probable sources of pollutants emissions to the study area, the elemental concentrations obtained, were subjected to Enrichment Factor Analysis (EF) and Principal Component Analysis (PCA). To further elucidate the relationship among pollutants in the sampling sites, correlations analysis, cluster analysis and Analysis of Variance (ANOVA) were carried out. The result of the mass concentrations of the particulates obtained revealed high base-line concentrations during both seasons of the sampling period. During the wet season, a concentration range of 833.33-1944.45 µgm-3 and 1111.11-1944.45 µgm-3 was obtained in the indoor and outdoor micro environment respectively. While, during the dry season, a concentration range of 1111.11-2777.78 µgm-3 and 1388.89-2222.22 µgm-3 was obtained in the indoors and outdoors. The PCA analysis identified road dust, combustion activities and marine as the predominant sources of pollutants emission in the environment. The results of the correlations analysis and cluster analysis were in agreement with the results of the EF and PCA. The results of ANOVA showed that, there was no spatial variation in the elemental concentration of most of the metals (P>0.05). In conclusion, results obtained revealed that, pollutants concentration in the study area were higher than air quality standard limits.